CFS nano-enzyme and application thereof in preparation of CFS-ion-MN wound repair microneedle patch
By loading CFS nanoenzymes and metal ions in the PVP/PVA microneedle system, the antibacterial agent is delivered transdermally by using microneedle technology, the penetration and drug resistance of nanoenzymes in wound healing are solved, and the bacteria are achieved Effective antibacterial and wound healing significantly accelerate the healing process.
Patent Information
- Application Number
- CN202411373828.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The prior art is difficult to penetrate the stratum corneum when using nanoenzymes to treat bacterial infection wounds, the ROS has a short lifespan, a short diffusion distance, and enhanced bacterial resistance, which affects the efficacy.
A PVP/PVA microneedle delivery system was designed to load CFS nanoenzymes and metal ions (Co2+ and Fe3+), and the antibacterial agent was delivered transdermally to the dermis layer through microneedle technology. CFS nanoenzymes catalyze H2O2 to generate ROS, combined with Co2+ and Fe3+ inhibit IL-17 and NF-κB signaling pathways and promote wound healing.
Effective antibacterial and wound healing of drug-resistant bacteria has been achieved, reducing the toxicity to normal cells, avoiding the problem of bacterial resistance, and significantly accelerating the wound healing process.
Smart Images

Figure CN119240801A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of medical materials, and specifically relates to a CFS nanozyme and an application thereof in preparing a CFS-ion-MN wound repair microneedle patch. Background Art
[0002] The skin is the body's first line of defense, protecting it from external bacteria. Once the skin is damaged, bacteria can invade the body. Bacterial infection is a common problem in the wound healing process. Bacterial invasion can aggravate inflammation and delay the wound healing process. With the abuse of antibiotics, bacterial resistance continues to increase, posing a serious threat to human health. Therefore, the development of new antibacterial agents to improve their efficacy in healing bacterially infected wounds is an important challenge currently faced. With the penetration and continuous development of nanotechnology in the antibacterial field, nanomaterials are gradually used to replace antibiotics.
[0003] Nanozymes are nanomaterials with enzyme-like properties. They have the advantages of being cheap, stable, and mass-produced. Through the bactericidal mechanism of catalyzing the production of ROS, they can avoid the production of drug-resistant bacteria when treating bacterially infected wounds. However, excessive ROS can damage normal cells, so it is necessary to balance the generation and removal of ROS. In addition, some studies have shown that some metal ions (such as zinc, magnesium, cobalt, etc.) can promote cell proliferation and angiogenesis (Wang Jiani, Chen Junyu. Mechanism of metal ion-induced angiogenesis and its application in bone tissue engineering [J]. Chinese Journal of Tissue Engineering Research, 2024, 28(5): 804-812). 2+ and Fe 3+ are essential trace elements for the human body, and they are involved in cell proliferation and differentiation. Cobalt is known to simulate hypoxia and cause angiogenesis. For example, Nandin et al. synthesized CoNZ with excellent enzyme-like activity and ion release, which can activate HIF-1α and promote angiogenesis, and is of great significance in promoting diabetic wound healing (Nandin et al. Double hits with bioactive nanozyme based on cobalt-doped nanoglass for acute and diabetic wound therapies through anti-inflammatory and pro-angiogenic functions. Bioactive Materials). However, Co 2+ and Fe 3+ The impact of co-regulation of inflammatory pathways and wound healing is currently unclear.
[0004] Although nanozymes are good potential alternatives to antibiotics, there are also some disadvantages in using nanozymes to fight bacterial infections: nanozymes are difficult to penetrate through the stratum corneum, and ROS have a short lifespan and diffusion distance. Microneedle technology (MN) is used in the field of transdermal drug delivery. It can pierce the stratum corneum and deliver drugs to the dermis, with the advantages of minimally invasive, painless, and efficient. Among them, soluble microneedles can encapsulate drugs / nanoparticles in a polymer matrix and completely dissolve after insertion into the skin. Combining soluble polymers polyvinyl alcohol (PVA) and polyvinyl pyrrolidone (PVP) into a PVA / PVP mixture has become a new tool for preparing biomaterials. There is a literature designing a PVP / PVA DMNP microneedle (MN) containing lidocaine for local anesthesia of the oral cavity. The tip of the microneedle is composed of polyvinyl pyrrolidone / polyvinyl alcohol (PVP / PVA), which can quickly dissolve and release lidocaine hydrochloride and achieve rapid anesthesia within 5 minutes. There is currently no literature publicly disclosing the use of microneedle technology to load CFS nanozymes and metal ions (Co 2+ and Fe 3+ ) products. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to solve the above technical problems and design a PVP / PVA microneedle drug delivery system loaded with CFS nanozymes and metal ions (Co 2+ and Fe 3+ ) to promote wound healing caused by drug-resistant bacteria.
[0006] Technical solution:
[0007] The present invention provides a CFS nanozyme, wherein the CFS nanozyme is a (Co3Fe)(S2)4 material, and the preparation method thereof is as follows: 1) Mix and dissolve Fe(NO3)3·9H2O, Co(NO3)2·6H2O and dimethylimidazole in ultrapure water, stir evenly and pour into a reactor for reaction. After the reaction is completed, collect the sample and dry it in an oven; 2) placing the sample 1 powder obtained in step 1) downstream of the tube furnace, taking sodium hypophosphite and placing it upstream of the tube furnace, and reacting under argon gas; 3) Step 2) The sample 2 after the reaction is completed is placed downstream of the tube furnace, and the sublimated sulfur is placed upstream of the tube furnace, and reacted under argon gas to obtain the final material (Co3Fe)(S2)4 nanozyme.
[0008] Furthermore, in step 1), the molar ratio of Fe(NO3)3·9H2O to Co(NO3)2·6H2O is 1:1-1:3.
[0009] Furthermore, in step 1), the molar ratio of Fe(NO3)3·9H2O and Co(NO3)2·6H2O to dimethylimidazole is 1:5-1:10.
[0010] Furthermore, the weight ratio of the sample 1 in step 2) to sodium hypophosphite is 1:5-1:20.
[0011] Furthermore, the mass ratio of the sample 2 in step 3) to the sublimated sulfur is 1:5-1:20.
[0012] Furthermore, the reaction temperature of step 1) is 100-180°C, and the reaction temperatures of step 2) and step 3) are 300-400°C.
[0013] The present invention also provides a CFS-ion-MN wound repair microneedle patch, which is prepared using the above-mentioned CFS nanozyme as a raw material, and the specific preparation method is as follows: 1) Prepare PVP-PVA gel with a mass fraction of 15-30wt%; 2) Take 10-20 ml of the PVP-PVA gel from step 1), 50-100 mg of the CFS nanozyme described in any one of claims 1-6, and 0.6-1.2 mg of Fe(NO3)3·9H2O and Co(NO3)2·6H2O, respectively. Heat in a water bath at 80-100°C and stir for 0.5-1h to mix and stir evenly to form a jelly; 3) 0.3-0.5 mL of the colloid obtained in step 2) is cast on the PDMS mold, and a vacuum pump is used to draw a vacuum to fill the gap at the needle tip; 4) Add 0.2-0.5 mL of the PVP-PVA solution from step 1) as the base and evacuate the mixture. After removing bubbles, place the mixture in a 30-60°C oven and dry for 3-8 hours to obtain CFS-ion-MN.
[0014] 5) Peel the CFS-ion-MN off the mold.
[0015] Furthermore, the mass ratio of PVP to PVA is 9:1-9:3.
[0016] Furthermore, the aqueous solution of Fe(NO3)3·9H2O and Co(NO3)2·6H2O contains Co 2+ and Fe 3+ The molar ratio is 1:1-1:3.
[0017] The present invention also provides application of the CFS-ion-MN wound repair microneedle patch in promoting wound healing.
[0018] Beneficial effects:
[0019] The primary purpose of the present invention is to provide a method for preparing CFS nanozyme, which can efficiently catalyze the decomposition of H2O2 to generate ROS, achieve good antibacterial properties against Gram-negative and Gram-positive bacteria in the presence of low concentrations of H2O2, and has broad-spectrum bactericidal properties, low toxicity to normal cells, and no problem of bacterial resistance, and is expected to be used in the field of antibiotic-free sterilization.
[0020] The CFS-ion-MN wound repair microneedle patch provided by the present invention can be used as a wound dressing to deliver antibacterial CFS nanozymes transdermally to the deep wound to effectively kill bacteria. CFS nanozymes can also inhibit inflammation in the body through superoxide dismutase-like activity, promote wound healing, and promote the inhibition of bacteria and healing of wounds of mice infected with Staphylococcus aureus. 2+ and Fe 3+ It can inhibit IL-17 and NF-κB signaling pathways, thereby accelerating wound closure. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 (a) X-ray diffraction spectrum and (b) scanning electron microscopy image of the CFS nanozyme prepared in Example 1.
[0022] Figure 2 This is the antibacterial property of the CFS nanozyme prepared in Example 1.
[0023] Figure 3 Synthesis and pictures of CFS-ion-MN.
[0024] Figure 4 This is the wound healing ability of CFS-ion-MN prepared in Example 5.
[0025] Figure 5 Transcriptomic analysis and qRT-PCR analysis of mouse wounds using CFS-ion-MN prepared in Example 5. DETAILED DESCRIPTION
[0026] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with embodiments and drawings. The embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.
[0027] Example 1 Preparation of CFS Nanozyme First, dissolve 1mmoL Fe(NO3)3·9H2O and 2mmoL Co(NO3)2·6H2O in 30mL ultrapure water (liquid A), then dissolve 18mmoL dimethylimidazole in 20mL ultrapure water (liquid B), pour liquid B into liquid A, stir rapidly for 15 minutes (liquid C), then pour liquid C into a 100mL reactor and react in a 120℃ oven for 24 hours. After the reaction is completed, centrifuge and wash three times with ethanol-water or methanol-water mixture, collect samples and dry them in a 60°C oven overnight; on the next day, take 100 mg of the dried powder and place it downstream of the tube furnace, take 1 g of sodium hypophosphite and place it upstream of the tube furnace, and react at 300°C for 2 hours under argon gas; after the reaction is completed, place the material downstream of the tube furnace, take 1 g of sublimated sulfur and place it upstream of the tube furnace, and react at 400°C for 1 hour under argon gas to obtain the final material (Co3Fe)(S2)4, which is abbreviated as CFS.
[0028] Figure 1 (a) is the X-ray diffraction spectrum (XRD) of (Co3Fe)(S2)4 prepared in Example 1, where the peaks of (Co3Fe)(S2)4 are located at 28, 32.5, 36.5, 40.1, 46.6, 55.3, 58, 60.6, 63.1, and 77.4, which are consistent with the standard card of (Co3Fe)(S2)4 (PDF#97-062-970). The XRD spectrum illustrates the successful synthesis of (Co3Fe)(S2)4. Figure 1 (b) SEM shows that CFS presents aggregated irregular spherical nanoparticles.
[0029] Example 2 Preparation of CFS Nanozyme First, dissolve 1mmoL Fe(NO3)3·9H2O and 3mmoL Co(NO3)2·6H2O in 30mL ultrapure water (liquid A), then dissolve 20mmoL dimethylimidazole in 20mL ultrapure water (liquid B), pour liquid B into liquid A, stir rapidly for 15 minutes (liquid C), then pour liquid C into a 100mL reactor and react in an oven at 180°C for 16 hours. After the reaction is completed, centrifuge and wash three times with ethanol-water or methanol-water mixture, collect samples and dry them in a 60°C oven overnight; on the next day, take 200 mg of the dried powder and place it downstream of the tube furnace, take 1 g of sodium hypophosphite and place it upstream of the tube furnace, and react at 350°C for 2 hours under argon gas; after the reaction is completed, place the material downstream of the tube furnace, take 1 g of sublimated sulfur and place it upstream of the tube furnace, and react at 400°C for 1 hour under argon gas to obtain the final material (Co3Fe)(S2)4, which is abbreviated as CFS.
[0030] Example 3 Preparation of CFS nanozyme First, dissolve 1mmoL Fe(NO3)3·9H2O and 1mmoL Co(NO3)2·6H2O in 30mL ultrapure water (liquid A), then dissolve 20mmoL dimethylimidazole in 20mL ultrapure water (liquid B), pour liquid B into liquid A, stir rapidly for 15 minutes (liquid C), then pour liquid C into a 100mL reactor and react in a 160°C oven for 18 hours. After the reaction is completed, centrifuge and wash three times with ethanol-water or methanol-water mixture, collect samples and dry them in an oven at 60°C overnight; on the next day, take 100 mg of the dried powder and place it downstream of the tube furnace, take 1 g of sodium hypophosphite and place it upstream of the tube furnace, and react at 300°C for 2 hours under argon gas; after the reaction is completed, place the material downstream of the tube furnace again, take 1 g of sublimated sulfur and place it upstream of the tube furnace, and react at 400°C for 1.5 hours under argon gas to obtain the final material (Co3Fe)(S2)4, which is abbreviated as CFS.
[0031] Example 4 Plate count method to test the antibacterial activity of CFS nanozyme Plate count method steps: Methicillin-resistant Staphylococcus aureus ( MRSA ) and multidrug-resistant Escherichia coli ( MDR E. coli ) was activated at 37°C, 150 rpm for 24 hours, and the bacterial solution was diluted to 1×10 -5 After cfu, 50 μL of bacterial solution was mixed with CFS in the presence or absence of H2O2 (50 μL, 0.5 mM) system and incubated for 2 hours in a shaker (37 min, 150 r). Liquid culture medium was used instead of material as a control group. Then, the mixed sample was spread on a solid culture dish and incubated at 37 ° C for 24 h before colony counting.
[0032] Figure 2 CFS nanozyme MRSA and MDR E. coli The results of the plate counting method were shown in Figure 2. Among them, compared with the control group and the H2O2 group, the CFS and CFS+H2O2 groups showed excellent antibacterial ability, indicating that CFS has good antibacterial properties, and the colony count showed that CFS had almost 100% antibacterial ability.
[0033] Example 5 Preparation method of CFS-ion-MN Figure 3In the synthesis process of CFS-ion-MN, PVP and PVA were mixed in a ratio of 9:1 to form a 20wt% gel (PVP-PVA). 20mL of the gel was taken, and 100mg of CFS, 1.2mg of Fe(NO3)3·9H2O and Co(NO3)2·6H2O were added thereto, and stirred at 90℃ for 1 hour to form a mixed colloid. Then 0.5mL of the solution was cast on the PDMS mold and vacuumed with a vacuum pump. Then 0.1mL of PVP-PVA gel was added as the base, vacuumed and defoamed, and then placed in a 40℃ oven to dry for 4 hours, and finally demolded.
[0034] Example 6 Preparation method of CFS-ion-MN PVP and PVA were mixed in a ratio of 9:2 to form a 20wt% gel (PVP-PVA). 20mL of the gel was taken, and then 100mg of CFS, 1.2mg of Fe(NO3)3·9H2O and 2.4mg of Co(NO3)2·6H2O were added, and stirred at 95℃ for 1 hour to form a mixed colloid. Then 0.5mL of the solution was cast on the PDMS mold and vacuumed with a vacuum pump. Then 0.1mL of PVP-PVA gel was added as a base, vacuumed and defoamed, and then placed in a 60℃ oven to dry for 3 hours, and finally demolded.
[0035] Example 7 Wound healing ability of CFS-ion-MN A wound model was established on the back of mice using Staphylococcus aureus as the infection species. A wound with a diameter of 6 mm was constructed on the back skin of mice after 5 days of adaptive feeding and infected with Staphylococcus aureus. The wound was treated with the CFS-ion-MN composite microneedle patch prepared in Example 5. The wounds were divided into the untreated group, the commercial dressing group, the CFS group (i.e., CFS nanozyme), the MN group (i.e., PVA-PVP gel), the CFS-MN group (i.e., without Co 2+ and Fe 3+ ) was used as the control group. The body weight and food intake of the mice were monitored daily, and the wound healing of the mice was observed and photographed for record.
[0036] Figure 4 This is a treatment picture of the CFS-ion-MN wound repair microneedle patch inhibiting bacteria and promoting wound healing. After 9 days of treatment, the wound healing rate of the control group and the MN group was the lowest, and large scabs were visible on the wound surface, followed by the wound dressing group and the CFS group. The CFS-MN and CFS-ion-MN groups had good healing effects, among which CFS-ion-MN had the best ability to promote wound healing.
[0037] Example 8 Transcriptomic Analysis and qRT-PCR Analysis of Mouse Wounds Wound tissues of mice were collected for transcriptomic analysis and qRT-PCR analysis. Figure 5 For the transcriptomic analysis of mouse wounds, the top 10 signaling pathways with the highest enrichment were selected for display based on the results of KEGG enrichment analysis, and it was found that the pathways related to differentially expressed genes related to the immune system included NF-κB and IL-17. Genes related to IL-17 and NF-κB were detected by qRT-PCR. The results showed that CFS-MN had a certain inhibitory effect on these genes. In addition, after the addition of metal ions, CFS-ion-MN could also significantly inhibit the expression of IL-17, NF-κB and their downstream targets. In summary, these findings indicate that CFS-ion-MN can inhibit inflammation through the IL-17 and NF-κB signaling pathways, thereby further improving the proliferation and angiogenesis of keratinocytes to accelerate wound healing in mice.
[0038] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A CFS nanozyme, characterized in that: The CFS nanozyme is a (Co3Fe)(S2)4 material, and its preparation method is as follows: Fe(NO3)3·9H2O, Co(NO3)2·6H2O and dimethylimidazole were mixed and dissolved in ultrapure water, stirred evenly and poured into a reactor for reaction. After the reaction was completed, the samples were collected and dried in an oven; The powder of sample 1 obtained in step 1) is placed downstream of the tube furnace, and sodium hypophosphite is placed upstream of the tube furnace to react under argon gas; Step 2) The sample 2 after the reaction is completed is placed downstream of the tube furnace, and the sublimated sulfur is placed upstream of the tube furnace, and reacted under argon gas to obtain the final material (Co3Fe)(S2)4 nanozyme.
2. The CFS nanozyme according to claim 1, characterized in that Step 1) The molar ratio of Fe(NO3)3·9H2O to Co(NO3)2·6H2O is 1:1-1:
3.
3. The CFS nanozyme according to claim 1, characterized in that Step 1) The molar ratio of Fe(NO3)3·9H2O and Co(NO3)2·6H2O to dimethylimidazole is 1:5-1:
10.
4. The CFS nanozyme according to claim 1, characterized in that: The weight ratio of the sample 1 to sodium hypophosphite in step 2) is 1:5-1:
20.
5. The CFS nanozyme according to claim 1, characterized in that: The mass ratio of the sample 2 to the sublimated sulfur in step 3) is 1:5-1:
20.
6. The CFS nanozyme according to claim 1, characterized in that: The reaction temperature of step 1) is 100-180°C, and the reaction temperature of step 2) and step 3) is 300-400°C.
7. A CFS-ion-MN wound repair microneedle patch, characterized in that: The CFS nanozyme according to any one of claims 1 to 6 is used as a raw material for preparation, and the specific preparation method is as follows: 1) Prepare PVP-PVA gel with a mass fraction of 15-30wt%; 2) Take 10-20 ml of the PVP-PVA gel from step 1), 50-100 mg of the CFS nanozyme described in any one of claims 1-6, and 0.6-1.2 mg of Fe(NO3)3·9H2O and Co(NO3)2·6H2O, respectively. Heat in a water bath at 80-100°C and stir for 0.5-1h to mix and stir evenly to form a jelly; 3) 0.3-0.5 mL of the colloid obtained in step 2) is cast on the PDMS mold, and a vacuum pump is used to draw a vacuum to fill the gap at the needle tip; 4) Add 0.2-0.5 mL of PVP-PVA solution as the base and evacuate the base. After removing bubbles, place the base in a 30-60°C oven and dry for 3-8 hours to obtain CFS-ion-MN. 5) Peel the CFS-ion-MN off the mold.
8. The CFS-ion-MN wound repair microneedle patch according to claim 7, characterized in that: The mass ratio of the PVP to PVA is 9:1-9:
4.
9. The CFS-ion-MN wound repair microneedle patch according to claim 7, characterized in that: The aqueous solution of Fe(NO3)3·9H2O and Co(NO3)2·6H2O contains Co 2+ and Fe 3+ The molar ratio is 1:1-1:
3.
10. Use of the CFS-ion-MN wound repair microneedle patch according to any one of claims 6 to 9 in promoting wound healing.
Citation Information
Patent Citations
Method for synthesizing bimetal sulfide Co8FeS8 / N-C polyhedron nano-material by ZIF-67 derivation
CN109473651A
A two-dimensional transition metal chalcogenide, its preparation method and application
CN110697793B
Micro-needle patch for promoting healing of diabetic wound and preparation method of micro-needle patch
CN115708817A
F-FeNC-GO antibacterial composite nano-enzyme and preparation method thereof
CN117065009A
Low-temperature-resistant iron monatomic nano-enzyme, preparation method thereof and application of low-temperature-resistant iron monatomic nano-enzyme in virus resistance
CN117225440A
